Awareness of Building Information Modelling (BIM) Among Construction Practitioners in Johor - ROSELI, FARIS AIMAN; ABAS, NOR HASLINDA (Recent Trends in Civil Engineering and Built Environment, 2023)
Building information modelling (BIM) is an innovative technique in the architectural,engineering, and construction (AEC) sector that has spread worldwide. However, the large percentage of AEC firms are not interested in BIM due to the challenges and barriers they would encounter in implementing the technique. Due to that, this study looks into the barriers of BIM implementation in the Malaysian AEC building sector in the Johor Bahru area, as well as the driving forces that will be used to overcome the challenges. The data was collected using a questionnaire survey method and analysed using SPSS. Other than that, this study are also to explore the awareness of BIM among the construction duty holders in Johor such as client, architect, consultant and contractor. The results shows that the overall cost and investment required to implement BIM are among the lowest and the major barriers of BIM implement are the lack of well-trained people which was the highest average mean.